Pengaruh PjBL-STEM terhadap Kemampuan Pemecahan Masalah Matematis pada Materi Untung-Rugi melalui Proyek Kompos - Hidayah, Aurora; Lestari, Wahyu; Zaif Zairozie, Athar (Program Studi Pendidikan Matematika FIP UNHASY, 2026)
This study aims to analyze the effect of implementing the Project-Based Learning integrated with STEM (PjBL-STEM) model on students’ mathematical problem-solving skills in the social arithmetic topic, specifically the profit and loss subtopic, through a project on making natural compost. The study employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The study population consisted of all eighth-grade students at SMP Negeri 1 Gading for the 2025/2026 academic year, with Class VIII B serving as the experimental group (26 students) and Class VIII A as the control group (27 students). Research instruments consisted of pretest posttest tests and student response questionnaires. Data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and N-Gain. The results showed a significant difference between the experimental and control classes (Sig. 0.000 < 0.05). The posttest average for the experimental class (89.65) was higher than that of the control class (73.15). The N-Gain value was 0.78 (high category), and the student response rate was 86.4% (very good category). Thus, the PjBL-STEM model is effective in enhancing students’ contextual and meaningful mathematical problem-solving skills